2012
DOI: 10.5194/nhess-12-1295-2012
|View full text |Cite
|
Sign up to set email alerts
|

Flash floods and debris flow in the city area of Messina, north-east part of Sicily, Italy in October 2009: the case of the Giampilieri catchment

Abstract: Abstract. This paper concerns the analysis of the 1 October 2009 flash flood and debris flow event caused by a very intense rainfall concentrated over the Messina area. The storm caused severe flash floods in many villages around the city of Messina, such as Giampilieri, Scaletta Zanclea, Altolia Superiore and Molino, with 38 casualties and significant damages to property, buildings, roads and bridges estimated close to 550 million Euro. The main focus of this work is to perform a post event analysis, putting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Aronica et al (2012) showed that a generalized extreme value (GEV) simple scaling model described well the distribution of annual maximum series of rainfall for the study region. The GEV simple scaling distribution of the rainfall rate r F (d) can be determined as…”
Section: Coupling the Slope Stability Model With The Generalized Extrmentioning
confidence: 99%
See 2 more Smart Citations
“…Aronica et al (2012) showed that a generalized extreme value (GEV) simple scaling model described well the distribution of annual maximum series of rainfall for the study region. The GEV simple scaling distribution of the rainfall rate r F (d) can be determined as…”
Section: Coupling the Slope Stability Model With The Generalized Extrmentioning
confidence: 99%
“…The floodplain is densely urbanized by the municipality of Giampilieri Superiore village (Aronica et al, 2012). A dense network of forest road is reported for the catchment (Fig.…”
Section: Study Area and Model Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent past, many Italian regions were affected by natural catastrophes caused by these extreme rainfall events (Aronica et al, 2012). These facts led to great focus being given to the prediction and creation of the alert systems to avoid or, at least, to reduce the occurrence of this type of catastrophes.…”
Section: Introductionmentioning
confidence: 99%
“…Flash floods are one of the most significant natural hazards in Europe, causing serious risk to life and the destruction of buildings and infrastructure Aronica et al, 2012). The potential for flash-flood casualties and damages is also increasing in many regions due to social and economic development bringing pressure on land use (Marchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%